Case Report: A 3D-Printed Surgical Guide for Breast-Conserving Surgery After Neoadjuvant Chemotherapy - Wu, Zhen-Yu; Kim, Guk Bae; Lee, Sangwook; Choi, Seung Hyun; Kim, Namkug; Ko, BeomSeok (Frontiers in Oncology, 2021)
Background: A challenging problem for patients undergoing breast-conserving surgery after neoadjuvant chemotherapy (NACT) is the accuracy of preoperative tumor localization. After chemotherapy, the original tumor is likely to shrink or scatter dramatically or even show complete remission. For breast-conserving surgery, the development of a guidance device to accurately estimate the resection range is imperative. Case Presentation: We produced a three-dimensional (3D)-printed breast surgical guide (BSG) based on prone and supine magnetic resonance imaging (MRI). This device was tested in a patient who underwent breast-conserving surgery after NACT. The tumor shrunk substantially after NACT on both ultrasonography and MRI. However, identifying the target tumor area using the pre-NACT MRI was feasible and the tumor was safely removed with clear resection margins. Conclusion: The BSG has several advantages over conventional methods for tumor localization after NACT. In particular, the BSG provided precise quantitative MRI information about the tumor area.